Legal Liability of Expedition Service Companies for Loss of Consumer Goods During the Transportation Process at J&T Express CP Tukad Bilok Sanur Kauh Denpasar - Oktavina, Sinta; Marheni, Lily (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This research discusses the form of responsibility of expedition companies for the loss of consumer goods during the transportation process. The transformation of the market from a traditional model to a digital model through the internet has led to a significant increase in demand for expedition services. This condition has encouraged the emergence of a number of shipping service companies in Indonesia, one of which is J&T Express. This research applies a non-doctrinal juridical sociological approach. Based on the results of interviews and data analysis related to incidents of loss of goods belonging to J&T Express service users, it is found that the company has fulfilled its obligations by providing compensation or compensation for the loss of goods experienced by consumers. J&T Express service users who experience loss of goods have several options to take legal action, namely by options to take legal action, namely by filing a lawsuit or claim against J&T Express through non-litigation, which is a form of direct dispute resolution without going to court, or through litigation involving legal proceedings in court. Until now, based on the information obtained, there has never been a dispute resolution through litigation at J&T Express CP Tukad Bilok Sanur Kauh Denpasar.